Pengaruh Variabel Ekonomi Makro Pada Nilai Intrinsik Saham - Putra Sadia, I Komang Gede Darma; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p28, 2019)
The purpose of this study was to find out and obtain empirical evidence of the effect of the rupiah exchange rate and gross domestic product on the intrinsic value of shares. The population of this study is non-financial companies listed on the Indonesia Stock Exchange for the period 2016-2017. The data sources used in this study are secondary data obtained in the annual reports of companies listed on the Indonesia Stock Exchange by accessing the site www.idx.co.id and the company's website. The sampling technique used was purposive sampling with a total sample of 283 companies in 2 years, so that in total 566 total observations were obtained. The data analysis used in this study is multiple linear regression analysis. Based on the results of the analysis it was found that the rupiah exchange rate variable had a negative effect on the intrinsic value of shares. While the gross domestic product variable has a positive influence on the intrinsic value of shares. Keywords : Price Earning Ratio, Rupiah Exchange Rate, Gross Domestic Product